3m-(14-4m)+3(m+7)-6=

Simple and best practice solution for 3m-(14-4m)+3(m+7)-6= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3m-(14-4m)+3(m+7)-6= equation:


Simplifying
3m + -1(14 + -4m) + 3(m + 7) + -6 = 0
3m + (14 * -1 + -4m * -1) + 3(m + 7) + -6 = 0
3m + (-14 + 4m) + 3(m + 7) + -6 = 0

Reorder the terms:
3m + -14 + 4m + 3(7 + m) + -6 = 0
3m + -14 + 4m + (7 * 3 + m * 3) + -6 = 0
3m + -14 + 4m + (21 + 3m) + -6 = 0

Reorder the terms:
-14 + 21 + -6 + 3m + 4m + 3m = 0

Combine like terms: -14 + 21 = 7
7 + -6 + 3m + 4m + 3m = 0

Combine like terms: 7 + -6 = 1
1 + 3m + 4m + 3m = 0

Combine like terms: 3m + 4m = 7m
1 + 7m + 3m = 0

Combine like terms: 7m + 3m = 10m
1 + 10m = 0

Solving
1 + 10m = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-1' to each side of the equation.
1 + -1 + 10m = 0 + -1

Combine like terms: 1 + -1 = 0
0 + 10m = 0 + -1
10m = 0 + -1

Combine like terms: 0 + -1 = -1
10m = -1

Divide each side by '10'.
m = -0.1

Simplifying
m = -0.1

See similar equations:

| 2(3v+8)= | | -2(x+4)=3x-8+5(2x+2) | | =-4+8(y-4)-7-5(x+2)+3y | | 5+5y=4y-4 | | 7a+4-4a+4=8a-2+a | | y=-b+15 | | (a+3)*(2a-1)=15 | | y=-5x+-9 | | 3x^2-5=-152 | | 4(2x-6)+5x=54 | | 2(12w+6)+2w=103 | | 3(4x+5)=-32+11 | | 2x-1=4x-9 | | 8y=9x-288 | | 5=2g-4 | | -3+yi=x+6 | | (7-4i)(2+i)= | | 7=3x+16 | | -16t^2+32t+12=0 | | 18x-(-6x)+49-(-31)-7x= | | 9e^10(x)=45 | | 6-8p=2 | | 5a(2a-5)=0 | | -4.6(2x-5)+7=2(5x+9) | | 3ln(x)=0 | | 3x=-4+2 | | (X-8)+(9X-327)+(4X-71)=180 | | 10-3(x+6)+5x=4 | | -54=-18s | | 4y-4x=36 | | 3x+17=2(4x+3) | | x-2(5x)=22 |

Equations solver categories